2017
DOI: 10.1016/j.snb.2017.05.169
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical biosensor platform for TNF-α cytokines detection in both artificial and human saliva: Heart failure

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 26 publications
0
58
0
Order By: Relevance
“…socio-demographic, clinical examination, medical condition, lab tests, medication intake, phenotypic data, sensor data) along with machine learning techniques are presented in [24,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]49]. Recent studies have identified certain biomarkers which strongly correlate with the HF severity, progression and mortality [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81], while the progress in analytical chemistry and biosensor development allowed their detection in saliva and breath [82][83][84][85] with prominent merits due to the easy and non-invasive sample collection. The Event prediction module aims to inform the experts about the possible presence of adverse events (relapses and mortality): (i) by introducing saliva and breath biomarkers into the adverse event prediction process, (ii) based on a machine le...…”
Section: Event Prediction Modulementioning
confidence: 99%
“…socio-demographic, clinical examination, medical condition, lab tests, medication intake, phenotypic data, sensor data) along with machine learning techniques are presented in [24,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]49]. Recent studies have identified certain biomarkers which strongly correlate with the HF severity, progression and mortality [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81], while the progress in analytical chemistry and biosensor development allowed their detection in saliva and breath [82][83][84][85] with prominent merits due to the easy and non-invasive sample collection. The Event prediction module aims to inform the experts about the possible presence of adverse events (relapses and mortality): (i) by introducing saliva and breath biomarkers into the adverse event prediction process, (ii) based on a machine le...…”
Section: Event Prediction Modulementioning
confidence: 99%
“…Artificial saliva (AS) has been prepared by dissolving 0.6 g/L Na2HPO4, 0.6 g/L anhydrous CaCl2, 0.4 g/L KCl, 0.4 g/L NaCl, 4 g/L mucin and 4 g/L urea in deionized water, adjusted to pH 7.2 by adding NaOH, sterilized by autoclaving and stored at −4 °C until use [5,6]. Antibodies and antigens were diluted in PBS buffer (pH 7.4), aliquoted at 5 mg/mL and 50 µg/mL respectively, then stored at −20 °C according to the protocol provided by the supplier.…”
Section: Artificial Saliva Preparationmentioning
confidence: 99%
“…Finally, the device has been cleaned for 30 min under UV-ozone to remove all organic contamination. Subsequently CMA molecules have been electrochemically deposited onto gold WEs by using cyclic voltammetry (CV) technique [5,6]. The biosensor platform was then rinsed and the terminal carboxylic acid (-COOH) groups of CMA were activated in a solution of NHS/EDC (0.1 M/0.4 M) for 1 h at room temperature.…”
Section: Bio-functionalization Of Gold Surfacementioning
confidence: 99%
“…The real‐time physiological surveillance is widely used in health monitoring and disease diagnosis for critical patients and persons with disabilities. The traditional monitors usually require mounting of sensors on the body and restrict patients’ motility and daily activities . The low adaptability and convenience impose a limitation on the development of health monitoring.…”
Section: Introductionmentioning
confidence: 99%